Symbolic Value and Social Function of Panai Money in Bugis Wedding Rituals - Anastasyia Rahmadina; Yunus Yunus (Journal of Islamic Studies and Civilization, 2024)
This study aims to examine the symbolic values and social functions of the dowry tradition in Bugis wedding rituals, by highlighting its integration with Islamic principle, especially maqashid al-syariah. This study uses a qualitative approach with primary data sources obtained through in-depth interviews with traditional leaders, religious leaders, and community leaders. The results of the study indicate that the dowry tradition in Bugis weddings contains deep symbolic values and carries out significant social functions in strengthening family ties and preserving customs. Furthermore, this study identified that the integration of Maqashid Al-Syariah values in Bugis wedding practices is going well through the Islamization of culture. Bugis wedding traditions are not found to be in conflict with Islamic law and are believed to bring benefits to husband and wife. This marriage custom is categorized as al-'dah as-sahihah or al-urf as-sahih, which is a good custom that can be used as a legal consideration based on the fiqh principle of al-adah muhakkamah. This study concludes that a deep understanding of the symbolic value and social function of dowry money within the framework of Islamic values provides a rich perspective on the harmony between local traditions and religious teachings.